Metodologias ativas no ensino de biologia celular por meio de uma sequência didática: desafios e possibilidades - Silva, Carlos Henrique Soares da (2023)
This research aimed to analyze to what extent the introduction of a Didactic Sequence articulated to Active Methodologies, in the Teaching of Cellular Biology, contributes to the learning of this content by high school students. A research with a qualitative approach of the pedagogical intervention type was carried out, with Biology teachers and students regularly enrolled in the 3rd year of High School in a Full-Time school of the State education network, located in the municipality of Icó/CE. With that, a Didactic Sequence was elaborated based on Active Methodologies to approach the contents of Cellular Biology. Three methodologies were used, namely: Flipped Classroom, Rotation by Learning Stations and Game-Based Learning. Data collection took place through the use of a semi-structured interview to search for data with the teachers, in addition to the projective interview and structured questionnaire for data collection with the students. Data analysis was performed using a Content Analysis approach. Data analysis was performed using a Content Analysis approach. The research results allow us to understand the challenges faced by professors and students in the teaching and learning process in Cell Biology. Students envision a close relationship between the existing difficulties in learning this discipline, with the way in which the contents are worked on in the classroom by the teachers. The Active Methodologies organized from the Didactic Sequence were evaluated by the students as dynamic, attractive, interactive, motivating and with important potential in the construction/enhancement of student learning. For all students, the Didactic Sequence was important and provided learning in relation to the contents. The challenges in experiencing the Didactic Sequence concern, above all, the time available to reconcile full-time school activities with the various demands of students' personal lives. From the teaching perspective, the challenges in planning and executing the Didactic Sequence are articulated between the time available for planning and the conditions for implementing the methodology, such as infrastructure, limited access to the internet, among others. Finally, the Didactic Sequence articulated from Active methodologies proved to be important in the teaching and learning process in Cell Biology by providing students with challenging activities, where students assumed active, autonomous, critical postures, and with that, enabled the construction /enhanced learning.